PERAN OXFAM DALAM KASUS PENINDASAN BURUH NIKE DI INDONESIA PADA TAHUN 2002-2012 - Dharmiasih, D.A. Wiwik; Kawitri Resem, Putu Titah; Mas Ayu AnggraeniÂ¬, Anak Agung Sagung (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2015)
ABSTRAK The case of Nike worker abuse began in the 1980s in several Asian countries, including Indonesia. This Nike worker abuse case in Indonesia has attracted reactions from local and international media. But the Indonesian government just has little attention for the Nike worker’s rights. Lack of attentions from Indonesian government has made Oxfam put their concern towards this case. Represented by its office in Australia and Indonesia, Oxfam tried to help the workers of Nike in Indonesia to achieve their rights. This research aims to describe the role of Oxfam in helping Nike’s workers in Indonesia from 2002 until 2012. This will be a qualitative-descriptive research and uses several concepts; Workers’ Rights, Workplace Violence, The Power of IOs, and Role of Human Rights NGO. This research found that Oxfam has roles in the efforts to help Nike workers in Indonesia which are providing information, lobbying, and providing assistance. Keywords: Nike, Oxfam, Worker, Abuse